The Impact Of Word Of Mouth And Brand Image On Purchase Decision: Study In Wall Street English Bandung - Putri, Denissa Aulia; Saputri, Marheni Eka (eProceedings of Management, 2023)
The large number of companies trying to expand their market has led to the importance of improving the quality of human resources in each region, one of which is communication. Therefore, English language skills are needed in the world of work because it is felt that it can improve one's communication skills. This research was conducted to determine the effect of word of mouth and brand image on purchasing decisions at one of the English language institutions in Bandung "Wall Street English". This research is quantitative in nature where the population used in this study is all members of Wall Street English Bandung. The variables in this study are word of mouth and brand image as the independent variables and purchasing decisions as the dependent variable. The regression results obtained show that there is a significant influence between word of mouth on purchasing decisions, and the results of subsequent regressions show that there is a significant influence between brand image and purchasing decisions. Based on the research that has been done, the two independent variables used have a significant impact on the dependent variable. The author suggests institutions to improve their quality which aims to increase the independent variables which will have an impact on the dependent variable.Keywords-word of mouth, brand image, purchase decision, english institute.